Adaptação na educação infantil de crianças com transtorno do espectro autista: relatos das famílias - Bueno, Luana Sposito (Universidade Federal de São Carlos, 2024)
Early Childhood Education, the first stage of Basic Education, includes the dimensions of caring, educating and playing. This phase is responsible for the child's first contact with a new environment, routine and people, moving them away from their family environment. Therefore, attention is needed during this period of adaptation, with the family being the protagonist and fundamental to its success. When you have a child with a disability or autism, family dynamics undergo changes, which must be based on the specific needs of the children. Thus, when entering Early Childhood Education, children with disabilities can cause insecurity in their parents. Establishing a relationship of trust between the family and the school becomes essential in this scenario. Therefore, the present study sought to analyze the school adaptation of children with disabilities, according to the families' opinions. The study design was descriptive and exploratory in nature. It had the participation of five parents, who carried out the interview in person or remotely, depending on their preference, guided by a semi-structured script. Through the results, it was understood that families enrolled their children with disabilities in Early Childhood Education with a view to their development and socialization. However, in some cases the adaptation process is still not successful, mainly because there are no exchanges with the institution before entry and during the child's stay at school. Legal services and adaptations to activities have not yet been observed, requiring the child himself to adapt to what was offered. The Early Childhood Education institution contributed to the development of children, from the parents' perspective. Furthermore, the effective relationship between the family and the school is not present, contributing to the feeling of distrust in relation to the work carried out by education professionals. For effective communication, it is important to invest in continued training of the school team, quick and easy contact between both parties and the promotion of an inclusive school culture, which provides space for parents to express their concerns, benefiting the school community as a whole
Adaptation in early early education of children with autistic spectrum disorder: reports from families
Keywords: Educação especial; Special education; Família; Family; Educação infantil; Child education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO